Health, human rights and mobilization of resources for health - Lie Reidar K (BMC, 2004)
Abstract Background There has been an increased interest in the role of a human rights framework to mobilize resources for health. Discussion This paper argues that the human rights framework does provide us with an appropriate understanding of what values should guide a nation's health policy, and a potentially powerful means of moving the health agenda forward. It also, however, argues that appeals to human rights may not necessarily be effective at mobilizing resources for specific health problems one might want to do something about. Specifically, it is not possible to argue that a particular allocation of scarce health care resources should be changed to a different allocation, benefiting other groups. Lack of access to health care services by some people only shows that something has to be done, but not what should be done. Summary The somewhat weak claim identified above together with the obligation to realize progressively a right to health can be used to mobilize resources for health.